Effects of poultry litter compost and chemical fertilizers on growth and yield of field grown sunflower (Helianthus annus L.) (Dhaka University Journal of Biological Sciences, 2021)
A field experiment was carried out in the research farm of Charfasson Govt. College, Bhola during Rabi season in 2016-2017 to evaluate the effects of poultry litter (PL) compost and NPK fertilizers on growth and yield of sunflower cv. BARI-2 (Keroni-2). Sixteen treatments were used with three replications each. Treatments were T1 : Control (-PL and –NPK), T2 : 1.5 ton PL/ha, T3 : 3.0 ton PL/ha, T4 : 4.5 ton PL/ha, T5 : N40P30K50 kg/ha, T6 : N80P60K100 kg/ha, T7 : N120P90K150 kg/ha, T8 : 1.5ton PL/ha + N40P30K50 kg/ha, T9 : 1.5 ton PL/ha + N80P60K100 kg/ha, T10 : 1.5 ton PL/ha + N120P90K150 kg/ha, T11 : 3.0 ton PL/ha +N40P30K50 kg/ha, T12 : 3.0 ton PL/ha + N80P60K100 kg/ha, T13 : 3.0 ton PL/ha + N120P90K150 kg/ha, T14 : 4.5 ton PL/ha + N40P30K50 kg/ha, T15 : 4.5 ton PL/ha + N80P60K100 kg/ha and T16 : 4.5 ton PL/ha + N120P90K150 kg/ha. Plant height (204.3 cm), number of leaf (44.8/plant), leaf area (376.4 cm2/plant), leaf area index (13.61), dry weight of stem (61.57 g/plant), root (12.66 g/plant), leaf (21.47 g/plant), petiole (8.7 g/plant), total dry matter production (134.0 g/plant) were found highest in T16 treatment. On the contrary, dry weight of inflorescence (32.6 g/plant), dry weight of seed (44.4 g/plant) and number of seeds (663/plant) were found highest in T13 and T14 treatments, respectively. Higher dry weight of 100 seeds (7.4 g) and diameter of inflorescence (54 cm) were also found in T13 treatment. Although highest value was found in T16 treatment, but T16 and T13 were not significantly (p > 0.05) different, it can be treated as best (T13) for future trial. The overall findings of this study indicated that organic fertilizer (poultry litter) in combination with inorganic fertilizers may be a good indicator to achieve better agronomic and yield parameters of sunflower plants under southern coastal edaphic conditions of Bangladesh.Dhaka Univ. J. Biol. Sci. 30(1): 49-57, 2021 (January)